ANALISIS EFEKTIVITAS DAN KONTRIBUSI PENERIMAAN PAJAK KENDARAAN BERMOTOR DI WILAYAH KABUPATEN GARUT - Lena Sri Rahayu Putri; Candra Sigalingging (Jurnal Studi Akuntansi Pajak Keuangan, 2024)
This study aims to find out how the effectiveness and contribution of motor vehicle tax revenues in the Garut Regency in 2019-2023 using effectiveness ratio analysis. The method in this study uses a descriptive method using a qualitative approach. Data collection techniques using library research and field research. Based on the results of the study, the average level of effectiveness of motor vehicle tax revenue in Garut Regency in 2019-2023 reached 96,14% and was categorized as effective, and the contribution of Motor Vehicle Tax to Regional Income in Garut Regency in 2019-2023 was categorized as moderate with average the average contribution rate reached 29.67%.